O ensino religioso na legislação educacional do Grão-Pará (1841 - 1887): um estudo introdutório - DOURADO, Viviane (2020)
This article results from a broader research on the History of Education in Pará. Its objective is to discuss the presence of religious teaching in the educational legislation of the Province of Pará, between 1841 and 1887, in order to understand its trajectory in the period. monarchic. For its elaboration we carried out a historical research and made a documentary analysis, having as primary sources nine educational norms of the period. From this, it was possible to understand the importance and influence of religious teaching, specifically the Catholic religion with the Crown, a reality that remained until the advent of the Republic in 1889